Removal of atrazine herbicide through granular activated carbon filters associated with microorganisms in drinking water treatment - Canevaroli, Miriam Ruiz; Macedo Lemos, Eliana Gertrudes de [UNESP]; Pires de Oliveira, Kelly Mari; Isique, William Deodato [UNESP]; Suarez, Yzel Rondon; Minillo, Alessandro (Assoc Brasileira Engenharia Sanitaria Ambiental, 2021)
Atrazine is a synthetic herbicide commonly used to control weeds and foliage in crops, and is a major contaminants of soil and water ecosystems. Many methods have been suggested to remove herbicides from drinking water. However, these methods are very costly, many have performance problems, produce a lot of toxic intermediates which are very harmful and dangerous. However, atrazine is susceptible to degradation by microorganism present in water, sediment, and sewage effluents. Considering these aspects, the main objective of the study was to investigate the biodegradation and filtration for using biological activated carbon (BAC) filters to remove atrazine, and their phylogenetic identification associated with these microorganisms. The results showed that atrazine was biodegraded by microorganism present in the biofilm, with removal over 80% in BAC filters. The microorganisms found integrate to the group of bacteria, composed by the genera Acinetobacter, Bacillus, Exiguobacterium, and Pseudomonas. This study allows us to infer the ability to biodegrade atrazine by bacteria present in BAC filters and capacity to remove herbicides by BAC filters, and the possible use of this technology as an alternative for the control and removal of this substance in water treatment.
Keywords: herbicides; bacteria; biofilm; water quality